2001
DOI: 10.1021/jm0102710
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Inhibiting Mode of AHPBA Derivatives against HIV-1 Protease and Building Predictive 3D-QSAR Models

Abstract: The Lamarckian genetic algorithm of AutoDock 3.0 has been used to dock 27 3(S)-amino-2(S)-hydroxyl-4-phenylbutanoic acids (AHPBAs) into the active site of HIV-1 protease (HIVPR). The binding mode was demonstrated in the aspects of the inhibitor's conformation, subsite interaction, and hydrogen bonding. The data of geometrical parameters (τ 1 , τ 2 , and τ 3 listed in Table 2) and root mean square deviation values as compared with the known inhibitor, kni272, 28 show that both kinds of inhibitors interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…QSAR analysis of anti-HIV drugs was performed on phosphoramidate derivatives [19] using Hansch analysis. Using the binding conformations of 3-amino-2-hydroxy-4-phenylbutanoicacids [20] into the active site of HIV-1 protease, highly predictive 3D-QSAR models were developed by CoMFA, CoMSIA, and HQSAR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR analysis of anti-HIV drugs was performed on phosphoramidate derivatives [19] using Hansch analysis. Using the binding conformations of 3-amino-2-hydroxy-4-phenylbutanoicacids [20] into the active site of HIV-1 protease, highly predictive 3D-QSAR models were developed by CoMFA, CoMSIA, and HQSAR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Since the phenyl group at the C-6 position of the pyrone ring was reported to improve the inhibitory activity, we assumed that the observed impressed activity could be due to the inserted heteroatoms. The compounds were docked into the binding site of HIV-1 PR structure using AutoDock3.0 program (Morris et al, 1998;Huang et al, 2002). Figure 2 from docking result showed that the phenyl group at C-6 position of the pyrone ring could fit the S 1 pocket very well as predicted.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the structures were docked to the binding sites of HIV-1 PR using AutoDock3.0 program (Morris et al, 1998;Huang et al, 2002), to investigate the interaction characteristics between respective compound and HIV-1 PR.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the HIV-1 PR mutants obliged us to apply very fast and precise techniques, able to predict the biological activity for the new HIV-1 PR inhibitors. QSAR (quantitative structureactivity relation) techniques [12][13][14], especially 3D-QSAR-CoMFA (Comparative Molecular Field Analysis) or 3D-QSAR-CoMSIA (Comparative Molecular Similarity Analysis) [15][16][17][18][19][20] proved to be very useful when the HIV-1 PR inhibitors potency are to be predicted. In the last years, a good correlation between the predicted and the observed biological activity for the HIV-1 PR cyclic urea inhibitors was reported [16,20,21].…”
Section: Introductionmentioning
confidence: 99%